PENERAPAN TEKNOLOGI INFORMASI DALAM SISTEM KEARSIPAN DI DIREKTORAT SARANA DAN PRASARANA (BASARNAS) - Salini, S. Sarwita; Pravitasari, Endyastuti; Manurung, Harris (Nindikayla Institute, 2025)
The implementation of information technology in the archival system of the Directorate of Facilities and Infrastructure at Basarnas aims to enhance document management efficiency through digitalization. Although an electronic administration system has been adopted, challenges remain, such as limited staff understanding, suboptimal integration of digital and manual systems, and manual archival disposal processes. To address these issues, staff training, paperless system development, automated archival disposal, and improved technological infrastructure are necessary. The MBKM internship program at Basarnas contributes to optimizing the digital archival system while providing students with hands-on experience. With continuous implementation and appropriate policy support, Basarnas' digital archival system can serve as a model for modernizing administration in government institutions, improving transparency, accountability, and public service effectiveness.